Concentrations of persistent organic pollutants in blood of the Spanish population: Temporal trend - González, Neus; Domingo, Jose L (Archives of Pharmacy, 2021)
The present article reviews the human biomonitoring studies conducted in Spain to assess exposure to persistent organic pollutants (POPs) such as polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs), polybrominated diphenyl ethers (PBDEs), and per- and polyfluoroalkyl substances (PFAS). In general terms, important variations in POPs concentrations between Spanish regions and specific populations were observed, while no associations between exposure to POPs and adverse health outcomes were found. Moreover, occupational exposure seems not to be a risk factor with regards to POPs exposure in the Spanish population. The present review highlights the importance of conducting human biomonitoring studies to find possible associations between POPs and adverse health effects.